2002
DOI: 10.1021/es010231l
|View full text |Cite
|
Sign up to set email alerts
|

Food Web Magnification of Persistent Organic Pollutants in Poikilotherms and Homeotherms from the Barents Sea

Abstract: Food web magnification of persistent organic pollutants (POPs) was determined for the Barents Sea food web using 615N as a continuous variable for assessing trophic levels (TL). The food web investigated comprised zooplankton, ice fauna and fish (poikilotherms, TL 1.7-3.3), and seabirds and seals (homeotherms, TL 3.3-4.2), with zooplankton representing the lowest and glaucous gull the highest trophic level. Concentrations of lipophilic and persistent organochlorines were orders of magnitude higher in homeother… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

25
183
10
2

Year Published

2005
2005
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 237 publications
(220 citation statements)
references
References 43 publications
25
183
10
2
Order By: Relevance
“…Relatively high d 15 N in black guillemot was also shown in previous studies (Fisk et al, 2001a;Hop et al, 2002). This indicates that black guillemot feeds higher in the food web, presumably on demersal or larger fish during pursuit diving, whereas kittiwake is a surface feeder on smaller pelagic fish, and occasionally on amphipods and euphausiids (Lønne and Gabrielsen, 1992;Mehlum and Gabrielsen, 1993).…”
Section: Group Isupporting
confidence: 80%
See 3 more Smart Citations
“…Relatively high d 15 N in black guillemot was also shown in previous studies (Fisk et al, 2001a;Hop et al, 2002). This indicates that black guillemot feeds higher in the food web, presumably on demersal or larger fish during pursuit diving, whereas kittiwake is a surface feeder on smaller pelagic fish, and occasionally on amphipods and euphausiids (Lønne and Gabrielsen, 1992;Mehlum and Gabrielsen, 1993).…”
Section: Group Isupporting
confidence: 80%
“…Increasing PCB levels with trophic position have been shown previously for seabirds and seals in Arctic marine food webs (Fisk et al, 2001a;Hop et al, 2002), and among Arctic seabirds from the Canadian Arctic (Buckman et al, 2004). In the present study, however, PCB levels were high in little auk occupying the lowest trophic position, and generally lower in black guillemot occupying the highest trophic position.…”
Section: Group Isupporting
confidence: 53%
See 2 more Smart Citations
“…Although it is not possible to specially compare the difference between Naito's results and the results of this study, a reasonable cause may be that the food web used in Naito's study excluded organisms such as seabirds or mammals at high trophic level. Several studies have demonstrated that the TMFs estimated based on food webs only including poikilotherms (fish) are usually lower than those estimated based on food webs including homeotherms (seabirds and mammals) (14,19,30). In addition, no obvious increasing trend was found on the TMFs of nonand mono-ortho PCBs with log Kow, considering that the regressions of concentration-trophic level for PCBs 77, 81, 126, 156, and 167 are not significant.…”
Section: )mentioning
confidence: 96%